액화천연가스를 활용한 개방형 랭킨 사이클에 적용한 냉열 발전의 최적화에 대한 연구 - 조정호(Jungho Cho); 김영우(Youngwoo Kim); 이중성(Joongsung Lee); 이종집(Jongjip Lee); 김동선(Dong Sun Kim) (한국수소 및 신에너지학회 논문집, 2017)
In this study, computer simulation and optimization works have been performed for an open-loop Rankine cycle to generate power using five cases of liquefied natural gas compositions. PRO/II with PROVISION V9.4 from Schneider electric company was used, and the Soave-Redlich-Kwong equation of the state model was utilized for the design of the power generation cycle. It was concluded that more power was obtained from less molecular weight liquefied natural gas since there was more volumetric flow rate with less molecular weight.